Adoption of Social Media Technologies and their Impact on Students’ Academic Performance: The only Way for Future Survival of Distance Education Students in Pakistan - Muhammad Arif (Pakistan Journal of Information Management & Libraries, 2016)
This study aims to investigate the adoption of social media technologies and their impact on academic performance of distance education students at Allama Iqbal Open University (AIOU), Islamabad-Pakistan. This study opted Combined-Technology Acceptance Model and Theory of Planned Behavior (C-TAM-TPB; Taylor & Todd, 1995) as theoretical model. Descriptive survey was administered to collect data with the help of self-reported structured questionnaire on 365 students, randomly selected from the targeted population. The response rate was 84.6%. Majority of the respondents were familiar and using the social media technologies frequently such as Facebook, YouTube and WhatsApp whereas Twitter was rarely used, also the students were having poor knowledge about the technology. Similarly, majority of the respondents were having average knowledge and familiarity in using Skype. The results of t-Test disclosed that gender difference existed in opinion towards frequency to use Facebook, Twitter, Wikipedia and WhatsApp only. The regression analysis also revealed that perceived usefulness, perceived behavior control, attitude towards use helped to enhance the students' actual use of social media technologies. However, perceived ease of use and subjective norms did not contribute in the use of the technologies. Furthermore, distance students' academic performance was increased by using the technologies. This study is delimited to five social media technologies; Facebook, Twitter, YouTube, Wikipedia, WhatsApp, and Skype only. To our best knowledge, this is first comprehensive study in distance education perspective which may provide guidelines to offer off-campus students services through effective utilization of the social media technologies.